Keterkaitan antara Dana Desa, Peran Serta Masyarakat, dan Pembangunan dari Perspektif Ekonomi Islam - Nisa Mutiara; Djoko Mursinto; Zainuddin Maliki (WADIAH, 2018)
Village Funds is already exist in 2015, one year after the implementation of Law Number 6/2014. The aim of this research is to analyze the relationship between the using of village funds and the village community participation to realize welfare in Islamic economic perspectives. This research is qualitative research with a case study approach of community participation in Megaluh Village, Jombang Regency, East Java Province, Indonesia. The implementation of Law Number 6 of the year 2014 as in line with the Village Funds in 2015 was able to encourage community participation in overall development processes ranging from planning, execution, supervision and utilization. The village community participation shows Islamic participation that the people involvement together with the goverment in development according to shari‟a to realize welfare (falah) that is in line with maqashid shari‟a.